Implementasi Algoritma $P Point Cloud Recognizer pada Pengenalan Angka Berbasis Game - Muhammad Farid Athar; Yohannes Yohannes; Yoannita Yoannita (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
More devices use gestures as their input method. Recognizing these gestures becomes more important for app development. One of the methods used for gesture recognition is Point Cloud Recognizer or $P. Gesture recognition can be used to recognize written characters like numbers or letters. Result of this recognition can be used for education involving apps, like games. This study is done by implementing $P in games to show that $P can be used as one of the methods for gesture recognition when developing games that need such features. In this study $P is implemented with the help of the game engine Unity with C# programming language. 3 sets of numerals 1 to 10 are used as data with $P configured to use 32 points. Total of 100 tests are done in the game resulting in 99% accuracy, showing $P is able to recognize the gesture well.